Case Report and Review of the Literature of a Rare Entity of a Uterine Fibroid: A Genital Rhabdomyoma. (January 2021) - Huesmann, Sophia T.; Wiegand, Miriam; Barth, Thomas F.; Mian, Elisabeth; Widschwendter, Peter; Janni, Wolfgang; Hancke, Katharina
Abstract : Extracardiac rhabdomyomas are rare benign tumors. According to histopathologic and clinical characteristics, they are divided into 3 subgroups: adult, fetal, and genital rhabdomyomas. Various adult extracardiac rhabdomyomas have been reported in the head and neck region, whereas genital rhabdomyomas are uncommon. Here, we report on a uterine genital rhabdomyoma in a 32-yr-old woman with secondary sterility. After myomectomy, the histopathologic analysis showed a slow cycling tumor with striated muscle differentiation and without any evidence of malignancy. Immunohistochemical staining proved coexpression of actin, caldesmon, and desmin. To the best of our knowledge, this is the first case of a uterine-based genital rhabdomyoma.